Prognostic impact of preexisting hypertension and high systolic blood pressure at admission in patients hospitalized for systolic heart failure. Issue 5 (May 2016) - Lee, Ji Hyun; Lee, Jun-Won; Youn, Young-Jin; Ahn, Min Soo; Ahn, Sung Gyun; Kim, Jang Young; Lee, Seung-Hwan; Yoon, Junghan; Oh, Jaewon; Kang, Seok-Min; Jeon, Eun-Seok; Choi, Dong-Ju; et al.
Abstract: Background: Higher systolic blood pressure (SBP) has been reported to be associated with a better prognosis in heart failure (HF) patients. This study aimed to investigate the prognostic impact of hypertension in patients hospitalized with systolic HF. Methods: Pooled analysis of data from three Korean observational studies was performed. Patients ≥18 years hospitalized with systolic HF (ejection fraction ≤45%) ( n  = 3538) were compared for the incidence of 1-year all-cause mortality according to the presence of preexisting hypertension and SBP quartiles on admission. Results: Patients with hypertension (prevalence, 51.6%) presented more often with diabetes (43.9% vs. 23.0%, p  < 0.001) and chronic kidney disease (14.1% vs. 5.7%, p  < 0.001). During the 1-year follow-up, patients with hypertension showed similar cumulative incidences of all-cause mortality as those without hypertension (8.3% vs. 8.4%, p  = 0.900). Conversely, patients with higher SBP on admission had a lower incidence of all-cause death (quartile 4 vs. 1: 6.7% vs. 11.3%, p for trend = 0.004). In the multivariate analysis, an increase in SBP of 10 mmHg was associated with an 8.5% risk reduction of all-cause death (hazard ratio: 0.915, 95% confidence interval: 0.853–0.981, p  = 0.013). Conclusions: Higher SBP on admission was independently associated with a lower risk of 1-year all-cause mortality in systolic HF.